Standardized mental status assessment of sports concussion - McCrea, M. (Clinical Journal of Sport Medicine, 2001)
Neurocognitive status is often considered the domain of neurologic functioning most sensitive to change following concussion, but the effects are often subtle and difficult to detect on routine clinical examination. Recent efforts have focused on the development of brief, standardized methods of mental status assessment for use by sports medicine clinicians to quantify the acute neurocognitive effects of concussion and objectively track postinjury recovery. Research has demonstrated the reliability, validity, and sensitivity of these measures in detecting concussion in athletes and providing empirical data for consideration in the context of other examination findings, neuropsychologic test data, and neuroimaging results. Standardized measures of mental status and other postconcussive symptoms are valuable tools to assist clinicians in the assessment and management of concussion, but should not be used as a replacement for medical evaluation or viewed as a stand-alone means for determining readiness to return to competition after injury.